EFEK BESARNYA PENGAPIAN BUSI TERHADAP UNJUK KERJA MESIN OTTO SATU SILINDER - Lukas Satrya; Abrar Riza; Steven Darmawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Along with the development of the times required vehicles that have good performance quality performance. One of them is by improving the quality of combustion that occurs in the combustion chamber. The research method used in this test is to determine the rotation and torque generated from each spark plug. Based on the data obtained, the torque and power generated by iridium spark plugs increases compared to nickel spark plugs, namely at 1800 RPM it produces 15 Nm of torque with 2.826 kW of power to 16 Nm of 3.0144 kW of power. From the test data, iridium spark plugs can increase ∆ BHP by 7%. But not with the specific fuel rate in the combustion engine produced by iridium spark plugs, the best results are higher than the specific fuel rate produced by nickel spark plugs, namely 2.0101 x 10-5 kg/kW.s at 3000 RPM rotation while the results the best specific fuel rate is 1.29 x 10-5 kg/kW.s at 2700 RPM rotation. This means that iridium spark plugs can increase the torque and power of the combustion engine because the combustion that occurs in the combustion chamber is faster so that combustion occurs in a rich state.